Suplementasi multi mikronutrien dibandingkan Fe-asam folat terhadap kadar hemoglobin dan berat badan ibu hamil anemia - Herta Masthalina; Mohammad Hakimi; Siti Helmyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: As a part of global strategy to prevent micronutrient deficiency in pregnant mothers, UNICEF recommends the use of multi-micronutrients supplements as an initial program in developing countries. Therefore, it is necessary to investigate the effect of multi-micronutrient supplementation on Hb level and weight gain of anemic pregnant women in Lombok Tengah District.Objective: To investigate the effect of multi-micronutrient compared to Fe – folic acid supplementation on Hb level and weight gain of anemic pregnant mothers.Method: This was a quasi-experimental study with non equivalent control group design. Subjects in the intervention group were given multi-micronutrient supplements provided by UNICEF, whereas subjects in the control group were given Fe – folic acid supplements. The supplements were given daily to the two groups for 91 days. Hb level and weight were measured before and after intervention.Results: Statistical analysis showed no significant differences (p=0.96) in Hb level and weight gain (p=0.454) between the two groups. The increase of Hb level and weight in the intervention group vs control group were 0,53±0,95 g/dL vs 0,89±1,15 g/dL and 4,89±2,71 kg vs 4,32±1,75 kg, respectively.Conclusion: There were no significant differences in Hb level and weight gain between pregnant mothers consuming multi-micronutrient supplements compared to those consuming Fe – folic acid supplements.